The Galactic Goal - Stilton, Geronimo (New York Scholastic, 2015)
The spacemice have received an invitation to participate in the intergalactic soccerix championship. It's a tournament for the most popular sport in space! But Geronimo doesn't even know how to play soccerix, let alone lead a team to victory against aliens with bizarre skills (like flying)! Can the spacemice team prevail.
Include Colored Illustration
Keywords: Children story book